Pengaruh Kepribadian Proaktif, Orientasi Kewirausahaan, Dan Pola Pikir Kewirausahaan Terhadap Perilaku Inovatif Pada Pengusaha Industri Kreatif Studio Foto Di Kabupaten Bekasi - Legiana, Viransa; Widodasih, R.R Wening Ken (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine the influence of Proactive Personality, Entrepreneurial Orientation and Entrepreneurial Mindset on Innovative Behavior in Creative Photo Studio Industry Entrepreneurs in the District. Bekasi using quantitative methods, data from this research was collected from 32 photo studio owners in the district. Bekasi. The sampling technique uses a non-probability sampling technique with a purposive sampling category. The analytical methods used in this research are data/instrument quality testing, classical assumption testing, hypothesis testing and multiple linear regression analysis with the help of SPSS 25 software as a tool for analysis. The results of this partial t test research show that the Proactive Personality variable has a significance value of (0.159) > (0.05), Entrepreneurial Orientation has a significance value of (0.001) < (0.05), Entrepreneurial Mindset has a significance value of (0.000) < (0 .05) so it can be concluded that the independent variable, namely Proactive Personality, has an influence but is not significant on Innovative Behavior. Entrepreneurial Orientation and Entrepreneurial Mindset have a significant and influential effect on Innovative Behavior. Meanwhile, the results of simultaneous testing (F test) have a significance value of (0.000) < (0.05) and a coefficient of determination (R2) of 0.873 or 87.3% of the Innovative Behavior variable is influenced by Proactive Personality, Entrepreneurial Orientation and Entrepreneurial Mindset while the remaining 12.7% is explained by other variables not used in this study.